2019
DOI: 10.1002/jmv.25462
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection among adults during influenza season: A frequently overlooked diagnosis

Abstract: Our objective is to assess the characteristics of respiratory syncytial virus (RSV) infection in adult patients and to establish differences with influenza viruses. Fiftyfour patients diagnosed with RSV and 198 with influenza were prospectively included. Compared with influenza, empirical antimicrobial therapy was more frequent in patients diagnosed with RSV, whereas antibiotic withdrawal at the time of diagnosis confirmation was lower (OR, 0.12; CI, 95% 0.01-0.90; P = 0.040). RSVpositive patients were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…The prescription rate was lowest in the influenza A H3 group, at 17% ( P = .036), and highest in the RSV group, at 28% ( P = .004). This result is in line with findings from studies from Spain, which found empirical antimicrobial therapy significantly more frequent in patients diagnosed with RSV than influenza during hospital stay 28,29 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prescription rate was lowest in the influenza A H3 group, at 17% ( P = .036), and highest in the RSV group, at 28% ( P = .004). This result is in line with findings from studies from Spain, which found empirical antimicrobial therapy significantly more frequent in patients diagnosed with RSV than influenza during hospital stay 28,29 …”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with findings from studies from Spain, which found empirical antimicrobial therapy significantly more frequent in patients diagnosed with RSV than influenza during hospital stay. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study assessing laboratory-confirmed hospitalised RSV cases in the USA found that only 44% had RSV-specific International Classification of Diseases discharge codes (in the first nine positions), suggesting that administrative data underestimate adult RSV-related hospitalisations 8. Furthermore, studies suggest that antibiotic use, morbidity and mortality are higher among RSV-positive than influenza-positive adult hospitalised patients9–11 and RSV patients are more likely to need hospital re-admission 12…”
Section: Introductionmentioning
confidence: 99%
“…[8] Furthermore, studies suggest that antibiotic use, morbidity, and mortality are higher among RSV-positive than influenza-positive adult hospitalized patients [9-11] and RSV patients are more likely to need hospital re-admission. [12]…”
Section: Introductionmentioning
confidence: 99%